2018
DOI: 10.1105/tpc.18.00547
|View full text |Cite
|
Sign up to set email alerts
|

A MPK3/6-WRKY33-ALD1-Pipecolic Acid Regulatory Loop Contributes to Systemic Acquired Resistance

Abstract: Plants induce systemic acquired resistance (SAR) upon localized exposure to pathogens. Pipecolic acid (Pip) production via AGD2-LIKE DEFENSE RESPONSE PROTEIN1 (ALD1) is key for SAR establishment. Here, we report a positive feedback loop important for SAR induction in We showed that local activation of the MAP kinases MPK3 and MPK6 is sufficient to trigger Pip production and mount SAR. Consistent with this, mutations in or led to compromised Pip accumulation upon inoculation with the bacterial pathogen pv DC300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 74 publications
(135 reference statements)
8
88
0
Order By: Relevance
“…We propose two main hypotheses to explain this phenomenon: (a) fungal signals influence plant responses to SA or (b) SA accumulation in ECM occurs in fungal hyphae and SA is not perceived by poplar cells. SA treatment of colonized LRs triggers the regulation of genes putatively involved in systemic defense (Data S9; Zhang et al, ; Wang et al, ; Guerra, Schilling, Sylvester, Conrads, & Romeis, ), suggesting that L. bicolor cannot suppress poplar responses to exogenous SA. However, we cannot exclude the possibility that fungal MiSSPs target endogenous SA signalling in poplar, similar to JA signalling (Plett et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We propose two main hypotheses to explain this phenomenon: (a) fungal signals influence plant responses to SA or (b) SA accumulation in ECM occurs in fungal hyphae and SA is not perceived by poplar cells. SA treatment of colonized LRs triggers the regulation of genes putatively involved in systemic defense (Data S9; Zhang et al, ; Wang et al, ; Guerra, Schilling, Sylvester, Conrads, & Romeis, ), suggesting that L. bicolor cannot suppress poplar responses to exogenous SA. However, we cannot exclude the possibility that fungal MiSSPs target endogenous SA signalling in poplar, similar to JA signalling (Plett et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…a), they have previously shown to be targeted by SYSTEMIC ACQUIRED RESISTANCE DEFICIENT 1 (SARD1) and CALMODULIN‐BINDING PROTEIN 60g (CBP60g) (Sun et al , ). A recent study just revealed that WRKY33 binds to the ALD1 promoter and positively regulates Pip accumulation (Y. Wang et al , ). Together, these findings imply that a regulatory connection between several known transcription factors, H3K4me3 histone marks and levels for defence gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, priming responses were compromised or lost in mutant lines of mpk3 and mpk6 (Beckers et al, 2009). MPK3 and MPK6 were shown to contribute to SAR via an ALD1-Pip regulatory loop (Wang et al, 2018b). Furthermore, an interplay between MPK and CPK signaling has been demonstrated for innate immune signaling in PTI (Boudsocq et al, 2010), where exemplary defense gene activation was shown to be either MPK-specific or CPK-specific, or to be controlled through joint MPK and CPK signaling.…”
Section: Cpk5 Protein Amount and Catalytic Activity Contribute To Thementioning
confidence: 98%